The Influence of Financial Literacy, Convenience, and Risk on Interest in Using Fintech Payments (PayLater) on Shopee - Erniwati; Winona Kumara Dewi; Syamsul Amar B; Syahrizal; Fitri Yulianis (www.amertainstitute.com, 2025)
This study aims to examine the influence between financial literacy, convenience and risk on interest in using fintech payment (paylater) at Shopee. The population in this study were students of the Faculty of Economics, Universitas Sumatera Barat. The sample in this study consisted of 90 respondents selected using the Simple Random Sampling technique.. Based on the results of the study, it can be concluded that financial literacy has a significant effect on interest in using fintech payment (paylater) at Shopee. Ease has a significant effect on interest in using fintech payment (paylater) at Shopee. Risk has a significant effect on interest in using fintech payment (paylater) at Shopee. Financial literacy, convenience and risk simultaneously affect the interest in using fintech payment (paylater) at Shopee. Where the variables of financial literacy and convenience have the most dominant influence on the interest in using fintech payment (paylater) at Shopee.